2022
DOI: 10.1111/poms.13615
|View full text |Cite
|
Sign up to set email alerts
|

For Better or For Worse: Impacts of IoT Technology in e‐Commerce Channel

Abstract: I nternet of Things (IoT) technology utilizes sensors and other internet-enabled devices to collect and share data. It is widely regarded as a disruptive technology that brings tremendous opportunities to supply chain members. This study uses a game-theoretical model to study an e-commerce setting in which an online platform provides IoT infrastructure and a manufacturer sells its products on the platform. Our work examines the interaction among the manufacturer's IoT investment decision, the platform's choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…e article [9] investigates whether uncommon incidence substances generate innovative user relations with expected perspective material, and it explains items that transmit news or media that occurs seldom, to create meaning and editorial engagement. A game-theoretical model is used in the work [10] to examine an e-commerce situation in which an Internet platform offers an IoT connection and a manufacturer sells its products on the platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e article [9] investigates whether uncommon incidence substances generate innovative user relations with expected perspective material, and it explains items that transmit news or media that occurs seldom, to create meaning and editorial engagement. A game-theoretical model is used in the work [10] to examine an e-commerce situation in which an Internet platform offers an IoT connection and a manufacturer sells its products on the platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, when there are sufficient returns, the retailer’s channel selling cost does not affect the manufacturer’s remanufacturing decision. Finally, Sun and Ji ( 2021 ) revealed how technology costs can impact manufacturer and channel performance. Their elaboration, in which an online platform provides IoT infrastructure and a manufacturer sells its products on the platform, surprisingly found that both manufacturer and channel performance could be negatively affected by an increase in the value of IoT technology in certain situations.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Chen et al [ 5 ] investigated an e-seller’s strategy of offering return-freight insurance in the reselling and agency selling formats, and found the conditions of offering return-freight insurance in the agency selling format are more stringent than in the reselling format. Sun and Ji [ 35 ] studied an e-commerce setting in which an online platform provides IoT infrastructure and a manufacturer sells its products on the platform. They examined the interactions among the manufacturer’s IoT investment decision, the platform’s pricing model choice, and the platform’s transfer payment strategy.…”
Section: Related Literaturementioning
confidence: 99%
“…It is worth noting that the quadratic effort cost function satisfies these conditions and has been widely used in previous studies. Following Li et al [ 22 ], Li et al [ 19 ], and Sun and Ji [ 35 ], we assume that . Then, the profit function of the internet celebrity can be formulated as follows: Note that k is sufficiently large.…”
Section: Model Preliminariesmentioning
confidence: 99%